Potato Zebra Chip: An Overview of the Disease, Control Strategies, and Prospects - Mora, Victoria; Ramasamy, Manikandan; Damaj, Mona B.; Irigoyen, Sonia; Ancona, Veronica; Ibanez, Freddy; Avila, Carlos A.; Mandadi, Kranthi K. (Frontiers in Microbiology, 2021)
Potato (Solanum tuberosum L.) is an important food crop worldwide. As the demand for fresh and processed potato products is increasing globally, there is a need to manage and control devastating diseases such as zebra chip (ZC). ZC disease causes major yield losses in many potato-growing regions and is associated with the fastidious, phloem-limited bacterium Candidatus Liberibacter solanacearum (CLso) that is vectored by the potato-tomato psyllid (Bactericera cockerelli Šulc). Current management measures for ZC disease mainly focus on chemical control and integrated pest management strategies of the psyllid vector to limit the spread of CLso, however, they add to the costs of potato production. Identification and deployment of CLso and/or the psyllid resistant cultivars, in combination with integrated pest management, may provide a sustainable long-term strategy to control ZC. In this review, we provide a brief overview of the ZC disease, epidemiology, current management strategies, and potential new approaches to manage ZC disease in the future.